METHODS OF OBTAINING AND CHARACTERISTICS OF DEPOSITED CATALYSTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
It is well known that catalysts are used in the processes of developing new materials, catalysts are used that allow for the targeted transformation of raw materials. Catalystsbased on rare, transitional and noble metals are widely used in industry. For more efficient use ofmetals, they are applied to various carriers that have a developed specific surface area, mechanicalstrength, resistance to aggressive environments, stability and inertia. Based on the above literaturedata, it is shown that catalysts obtained by physical methods have a higher conversion and catalyticactivity compared to catalysts obtained by classical methods, such as impregnation or reductionmethods. This article is devoted to a review of the literature on methods for obtaining catalystson carbon carriers. The analysis of literary sources is designed toselection of methods of targetedmodification of coals in Kyrgyzstan in order to obtain highly efficient carriers and synthesis ofdeposited catalysts.
Keywords: catalysts, carbon carriers, synthesis, catalytic activity.